Effects of marine microalgae and cyanobacteria towards the morphology and survival rate of zebrafish larvae, Danio rerio - Toh, En Chun (2018)
The zebrafish (Danio rerio) is becoming internationally recognized as a test model organsims representing animals as well as human. An experiment was conducted to study selected different microalgae and cyanobacteria extracts (Spirulina platensis, Monoraphidium sp., Halamphora sp., Chaetoceros sp. and Chattonella marina) on the D. rerio larvae morphology and survival rate. Samples of microalgae and cyanobacteria at stationary phase were extracted using 95% methanol and were exposed to D. rerio eggs at the concentrations of 0 ppm, 10 ppm, 20 ppm, 50 ppm and 100 ppm. The embryonic development was observed daily until hatched. The results showed that no significant differences between egg morphology were detected through the exposure from 0 ppm until 100 ppm. The experiment was then repeated through an increase of concentration up to 200 ppm. It was shown that a toxic Chattonella marina induced negative impacts towards the zebrafish larvae morphology causing deformation with low survival rate at (46.67%) compared to control treatment (0ppm, sterile distilled water) which have 100% survival rate. This indicated that the Chattonella marina is lethal towards the zebrafish larvae at high concentration.